2018
DOI: 10.3390/molecules23061261
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Chemical Profile in Agarwood Formation within One Year and Speculating on the Biosynthesis of 2-(2-Phenylethyl)Chromones

Abstract: Agarwood is highly valued for its uses as incense, perfume, and medicine. However, systematic analyses of dynamic changes of secondary metabolites during the process of agarwood formation have not yet been reported. In this study, agarwood was produced by transfusing the agarwood inducer into the trunk of Aquilaria sinensis, and changing patterns of chemical constituents, especially 2-(2-phenylethyl)chromones (PECs), in wood samples collected from the 1st to 12th month, were analyzed by GC-EI-MS and UPLC-ESI-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Chemical constituents of agarwood have been intensively studied by several research teams [ 1 , 3 , 13 ]. Different extraction methods have been developed to determine chemical composition of essential oils and related compounds from agarwood chips using GC, GC-MS, solid phase microextraction, GC-flame ionization detector, GC-olfactometry, or comprehensive two-dimensional gas chromatography (GC×GC) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical constituents of agarwood have been intensively studied by several research teams [ 1 , 3 , 13 ]. Different extraction methods have been developed to determine chemical composition of essential oils and related compounds from agarwood chips using GC, GC-MS, solid phase microextraction, GC-flame ionization detector, GC-olfactometry, or comprehensive two-dimensional gas chromatography (GC×GC) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chemical constituents of agarwood have been studied by several research teams [ 1 , 3 , 13 ]. Previous studies identified chemical constituents of agarwood essential oils or organic solvent extracts with column chromatography or spectroscopic techniques [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the PECs have only been found to be present in a few species of plants for example Bothriochloa ischaemum (Wang et al, 2001), Imperata cylindrical (Liu X. et al, 2013), Cucumis melo L. (Ibrahim, 2014), Gyrinops salicifolia (Shao et al, 2016), and Aquilaria species (Wu et al, 2012b; Yang et al, 2014a). Recently, a hypothetical scheme for the biosynthetic pathway of PECs was proposed by Liao et al (2018) based on in-dept analysis of agarwood chemical constituents using GC-EL-MS and UPLC-ESI-MS/MS methods. In their study, the PECs was found to be the major agarwood resin constituents, which is comprised mostly of flindersia-type 2-(2-phenylethyl) chromones (FTPECs).…”
Section: The Biosynthesis Pathways Of Agarwood Constituentsmentioning
confidence: 99%
“…In their study, the PECs was found to be the major agarwood resin constituents, which is comprised mostly of flindersia-type 2-(2-phenylethyl) chromones (FTPECs). The formation of FTPECs is further elucidated to be possibly catalyzed by type III polyketide synthase (PKs) through condensation of dihydro-cinnamoyl-CoA analogs and malonyl-CoA with 2-hydroxy-benzoyl-CoA to produce PEC scaffold that will subsequently be catalyzed by hydroxylases or O -methyltransferases (OMTs) to form structurally diverse FTPECs (Liao et al, 2018). Recent study showed that salinity stress could induce the biosynthesis of PECs in A. sinensis calli (Wang et al, 2016).…”
Section: The Biosynthesis Pathways Of Agarwood Constituentsmentioning
confidence: 99%